Differential influence of Pomphorhynchus laevis (Acanthocephala) on brain serotonergic activity in two congeneric host species - Tain, Luke (The Royal Society, 2006)
The physiological mechanisms by which parasites with complex life cycles manipulate the behaviour of their intermediate hosts are still poorly understood. In Burgundy, eastern France, the acanthocephalan parasite Pomphorhynchus laevis inverses reaction to light in its amphipod host Gammarus pulex, but not in Gammarus roeseli, a recent invasive species. Here, we show that this difference in manipulation actually reflects a difference in the ability of the parasite to alter brain serotonergic (5-HT) activity of the two host species. Injection of 5-HT in uninfected individuals of both host species was sufficient to inverse reaction to light. However, a difference in brain 5-HT immunocytochemical staining levels between infected and uninfected individuals was observed only in G. pulex. Local adaptation of the parasite to the local host species might explain its inability to manipulate the behaviour and nervous system of the invasive species.